2010
DOI: 10.1007/s11605-010-1207-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 18-Fluorodeoxyglucose Positron Emission Tomography on the Management of Pancreatic Cancer

Abstract: FDG-PET is not a suitable imaging modality for either diagnosis or preoperative treatment in pancreatic cancer patients. Since it is expensive, FDG-PET as a routine diagnostic tool in pancreatic cancer patients must be used with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…The significant relation between tumor size and SUV has been reported by many studies and in various organs, such as colon, 16,22 pancreas, 23 and breast. 24,25 On the other hand, in our study, SUV did not correlate with tumor growth as assessed by PCNA expression.…”
Section: Discussionmentioning
confidence: 80%
“…The significant relation between tumor size and SUV has been reported by many studies and in various organs, such as colon, 16,22 pancreas, 23 and breast. 24,25 On the other hand, in our study, SUV did not correlate with tumor growth as assessed by PCNA expression.…”
Section: Discussionmentioning
confidence: 80%
“…It was also recently reported that pancreases with PanIN can be imaged using standard FDG uptake in a mouse model 38. Several difficulties with applying FDG in clinical pancreatic cancer imaging have been identified39 and will probably limit the usefulness of this approach. In addition, while it was reported that urokinase plasminogen activator receptor could be used for targeting PDAC, amino-terminal fragment composed of 135 amino acid residue was needed to achieve efficient binding 40.…”
Section: Discussionmentioning
confidence: 99%
“…FDG-PET has the strength of a high specificity but a striking lack of sensitivity is reported regarding small liver metastases [35]. Therefore, FDG-PET is currently not the method of choice for resectability assessment of pancreatic cancer [13,36].…”
Section: Livermentioning
confidence: 99%